ANALISIS PREFERENSI KONSUMEN SEBAGAI DASAR PENENTUAN SEGMENTASI DI PERBANKAN SYARIAH (Studi Kasus PT Bank Muamalat Indonesia Cabang Solo) - Haryanto, Heru Purnomo & (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2010)
Abstract The objectives of this research are to analysis the preference of consumer on the syariah bank as base of segmentation and how the segmentation strategy is applied. There are three analysis for segmentation analysis: factor analysis, cluster analysis, and profiling analysis. The result of this research are by the factor analysis, there are six factors (location, park, funding, saving, motivation, and services), by cluster analysis, there are three cluster (location, benefit of product, and motivation), by profiling analysis, there are three segmentation area (geographic, psychographic, and behavioral). Keywords: Segmentation, cluster analysis, geographic segmentation, psychographic segmentation, behavioral segmentation